Physicochemical studies of novel sugar fatty acid esters based on (R)-3-hydroxylated acids derived from bacterial polyhydroxyalkanoates and their potential environmental impact - Snoch, Wojciech; Jarek, Ewelina; Milivojevic, Dusan; Nikodinovic-Runic, Jasmina; Guzik, Maciej (Frontiers in Bioengineering and Biotechnology, 2023)
Sugar fatty acids esters are popular compounds widely used in both the nutritional, cosmetic and pharmaceutical industries due to their amphiphilic structure and consequent ability to reduce the surface tension of solutions. Furthermore, an important aspect in the implementation of any additives and formulations is their environmental impact. The properties of the esters depend on the type of sugar used and the hydrophobic component. In this work, selected physicochemical properties of new sugar esters based on lactose, glucose and galactose and hydroxy acids derived from bacterial polyhydroxyalkanoates are shown for the first time. Values for critical aggregation concentration, surface tension variation and pH make it possible that these esters could compete with other commercially used esters of similar chemical structure. The investigated compounds showed moderate emulsion stabilization abilities presented on the example of water-oil systems containing squalene and body oil. Their potential environmental impact appears to be low, as the esters are not toxic to Caenorhabidtis elegans even at concentrations much higher than the critical aggregation concentration.